FORMULATION A NATURAL COSMETIC SCRUB OF DURIAN HUSK (DURIO ZIBETHINUS MURR.) AND THE CHARACTERISTIC TESTS) - Febriani, Yuyun; Yuliana, Tri Puspita; Hariadi, Puspawan; Gemantari, Baiq Maylinda; Minawati, Minawati (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
The high production of durian fruit gives an environmental problem if it is not used properly. Durian fruit skin contains flavonoids, phenolic compounds, saponins, and tannins which have antioxidant activity. Its antioxidant activity makes durian husk a candidate as a basic ingredient for natural cosmetics. Producing a formulation of scrub preparations as natural cosmetics based on the results of the characteristic test was the purpose in this research. Experimental research with a post-test design technique was carried out by making the changes of the concentration of durian husk as an active ingredient in the scrub preparations used in this study. The form of an oil-in-water cream scrub was used as the formulation in a change of concentration range of 1% (F1), 1.5% (F2), and 3% (F3) for each formula. Furthermore, the characteristic test was carried out which included organoleptic test, homogeneity test. pH test, viscosity test, spreadability test, and adhesion test. In this research also used statistica tests. The results showed that the best formulation is obtained from formulation 3 (F3) with a concentration of 3% durian rind. The characteristic test results include: stable organoleptic test for storage in terms of shape, color and odor; homogeneity test formed granules and there was no separation between the oil and water phases; Stable pH test according to skin pH at 5.05; spreadability test 7.3 cm; viscosity test 64 dPa.s; and 2.41 minutes of adhesion test. It pointed that all formulations fulfilled the requirements for topical scrubs in each characteristic test.